Terrorism and the state - Konrad, Kai A. (2002)
Abstract: "This paper considers terrorism as an extortion activity. It uses tools from the theory of extortion and from conflict theory to describe how terrorism works, why terrorism is a persistent phenomenon, why terrorism is a violent phenomenon, and how retaliation affects the outcome. The analysis highlights the importance of information aspects and discusses some aspects of the organizational design." (author's abstract)